1977
DOI: 10.1104/pp.60.3.402
|View full text |Cite
|
Sign up to set email alerts
|

Methionine-induced Ethylene Production by Penicillium digitatum

Abstract: Shake cultures, in contrast to static cultures of Penicillium digitatum grown in lquid medium, were induced by methionine to produce ethylene. The induction was concentration-dependent, and 7 mm was optimum for the methionine effect. In the presence of methionine, glucose (7 mM) enhanced ethylene production but did not itself induce ethylene production. The induction process lasted several hours, required the presence of viable mycelium, exhibited a lag period for ethylene production, and was effectively inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

1978
1978
2002
2002

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 11 publications
1
37
0
Order By: Relevance
“…The results on ethylene inhibition obtained in this study, with both the static and shake cultures of the fungus, in which ethylene is being produced from different precursors (3,4), show similarities to those obtained with higher plants (10,11). They support the hypothesis that these compounds inhibit ethylene production by irreversibly attaching to the ethylene-forming enzyme.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The results on ethylene inhibition obtained in this study, with both the static and shake cultures of the fungus, in which ethylene is being produced from different precursors (3,4), show similarities to those obtained with higher plants (10,11). They support the hypothesis that these compounds inhibit ethylene production by irreversibly attaching to the ethylene-forming enzyme.…”
Section: Resultssupporting
confidence: 72%
“…Determination of radioactivity, inoculation and incubation procedures, culture weight determination, and ethylene analyses were performed as previously described (3,15). Further details of techniques are described in the legends to the tables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 and 9) with the exception of the two hiah levels of gylcerol in Soil L. These results are in contrast to those reported by Hunt et al (1980) and Sutherland and Cook (1980) who reported that the addition of methionine had no effect on the oroduction of C 2 H 4 in their soils. Several other reports, however, agree that methionine sicmificantly increased C 2 H 4 production (Chalutz and Lieberman, 1977;Lynch. 1972;Lynch and Harper,1974).…”
Section: Control Me1hioninementioning
confidence: 83%
“…L-Methionine has been established as a precursor of ethylene in higher plants and several microorganisms (3,13,20). In contrast, an incubation of P. tricornutum with L-methionine (100 mm or 10 mm final concentration) for 24 h has no influence on the production of ethylene or the other hydrocarbons.…”
mentioning
confidence: 99%